Current trends in the management of ocular symptoms in Adamantiades-Behçet’s disease - Fouad R Zakka (Dove Medical Press, 2009)
Fouad R Zakka,1 Peter Y Chang,1 Gian P Giuliari,1 C Stephen Foster1,21Massachusetts Eye Research and Surgery institution (MERSI), Cambridge, Massachusetts, USA; 2Department of Ophthalmology, Harvard Medical School, Boston, Massachusetts, USAAbstract: Adamantiades-Behçet’s disease (ABD) is a multisystemic vasculitic disease. It is most prevalent in the Eastern Mediterranean countries and the Eastern region of Asia. Its effect on the eye can range from mild to debilitating, resulting in total blindness. A necrotizing and obliterative vasculitis affects both arteries and veins of organs. Recurrent attacks of uveitis, oral aphthous ulcers, skin lesions, and genital ulcers are common. Topical and systemic corticosteroids have been the mainstay in the treatment of ocular inflammation for many years; however, due to the several known side effects of corticosteroids and thanks to scientific advances, more novel approaches to ABD treatment have been emerging. Antimetabolites such as methotrexate and azathioprine have been utilized with the latter showing positive results. Chlorambucil has been utilized effectively for ocular manifestations of ABD. Interferon alpha has shown encouraging results in the management of refractory ocular inflammation associated with ABD, either alone or in combination with other immunosuppressive agents. Surgical interventions to deal with complications from ABD can be safely done if adequate control of inflammation is achieved peri-operatively. Early detection and aggressive treatment, when needed, have proven to be essential in the management of this relentlessly explosive disease.Keywords: Adamantiades-Behçet’s disease, Behçet’s disease, ocular inflammation, uveitis, immunomodulatory therapy, immunosuppressive therapy